2000
DOI: 10.1159/000025480
|View full text |Cite
|
Sign up to set email alerts
|

Actions of Melatonin in the Reduction of Oxidative Stress

Abstract: Melatonin was discovered to be a direct free radical scavenger less than 10 years ago. Besides its ability to directly neutralize a number of free radicals and reactive oxygen and nitrogen species, it stimulates several antioxidative enzymes which increase its efficiency as an antioxidant. In terms of direct free radical scavenging, melatonin interacts with the highly toxic hydroxyl radical with a rate constant equivalent to that of other highly efficient hydroxyl radical scavengers. Additionally, melatonin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
394
3
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(426 citation statements)
references
References 88 publications
(133 reference statements)
13
394
3
16
Order By: Relevance
“…(17); stabilize sleep-wake cycles (18). Melatonin stimulates several antioxidative enzymes (19) and acts on bone metabolism (20). The hormone exerts its effects both through activation of its receptors (21), through the circulating levels of the hormone or in a more autocrine/paracrine fashion near target tissues (22,23).…”
Section: Melatonin and Its Functionmentioning
confidence: 99%
“…(17); stabilize sleep-wake cycles (18). Melatonin stimulates several antioxidative enzymes (19) and acts on bone metabolism (20). The hormone exerts its effects both through activation of its receptors (21), through the circulating levels of the hormone or in a more autocrine/paracrine fashion near target tissues (22,23).…”
Section: Melatonin and Its Functionmentioning
confidence: 99%
“…The mechanisms of diabetes-related apoptosis are unclear. However, current studies have indicated that diabetes-mediated oxidative stres can induce apoptosis (Allan et al, 1992;Reiter et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have reported that acute aMT administration, an antioxidant and free radical scavenger (Antolin et al, 1996;Tan et al, 2000aTan et al, , 2000bTan et al, , 2002Turjanski et al, 2001), counteracted mitochondrial deficiencies in SAM mice (Okatani et al, 2001(Okatani et al, , 2002a(Okatani et al, , 2002b. The indoleamine and several of its metabolites are scavengers of free radicals and it is now considered a component of the endogenous antioxidant system (Reiter, 1998(Reiter, , 2000Tan et a., 2007).…”
mentioning
confidence: 99%